Density functional analysis of group 10 organometallic diphosphinito complexes for catalytic formation of C‐P bonds. Issue 12 (23rd February 2016) - Ellis, Matthew; Downey, Karen
Abstract : New group 10 metalloorganic complexes are proposed as the basis of new catalysts for the formation of carbon‐phosphorous bonds. Density functional theory (DFT) is applied, using multiple DFT functionals, to model molecular geometry as well as electron density distribution in the highest occupied molecular orbitals (HOMOs) expected to carry out a reductive catalytic cycle. DFT/M06 analysis predicts a robust planar geometry, regardless of alteration of major components. Precursors for rapid catalyst generation should begin with an electron‐withdrawing monodentate ligand. Palladium and platinum catalysts have lower chemical hardness, but the electron distribution in the HOMO of the nickel‐based catalyst is preferred for reductive catalytic mechanisms. Both electron density and chemical hardness, however, are affected by the choice of metal ion and the composition of the monodentate ligand bound to it. Group 10 metalloorganic complexes are modeled as precursors for generating new catalysts for a minimally wasteful method of forming bonds commonly found in biochemically active compounds. Suitable precursors have an accessible metal center, as well as significant the HOMO/LUMO involvement at the metal center. All complexes studied offer similar geometries, but precursor transformation into catalyst depends on the electron‐withdrawing ligand being exchanged. Catalyst turn over number is predicted to depend primarily on the central metal. © 2016 Wiley Periodicals, Inc. Abstract : Group 10 metalloorganic complexes are modeled as precursors for generating new catalysts for a minimally wasteful method of forming bonds commonly found in biochemically‐active compounds. Suitable precursors have an accessible metal center, as well as significant HOMO/LUMO involvement at the metal center. All complexes studied offer similar geometries, but precursor transformation into catalyst depends on the electron withdrawing ligand being exchanged. Catalyst turn over number is predicted to depend primarily on the central metal.